Designing TOD precincts: accessibility and travel patterns - Olaru, D.; Curtis, Carey (Editorial Board EJTIR, 2015)
This paper reports on a research study that investigated the travel behaviour of residents in three case study station precincts located along a new railway in Perth, Western Australia. The precincts were selected for comparison, representing the different development opportunities ranging from planned transit-oriented development (TOD) to station precincts acting primarily as origin stations or transit interchanges. Accessibility measures and the actual travel patterns of residents in each station precinct were compared, in order to consider the degree to which different station precinct designs have led residents to reduce their motorised travel and to substitute it with both public transport within the region, and walking or cycling within the local neighbourhood. We draw on two surveys: a household survey, including a travel diary, examining behaviours after the railway opened; a detailed survey measuring both local and regional accessibility using a suite of over 30 measures of multi-modal accessibility. The results highlight the dual role of public transport and land—use planning in changing mobility patterns, using a temporal perspective. We found a positive relationship between improvements to accessibility by public transport and residents reducing car-based travel. Residents also increased the spatial reach of their travel and many converted from uni-modal to multi-modal travellers. At the local level (station precinct), however, we found an accessibility mismatch between infrastructure and proximity to facilities, whereby neighbourhoods with a high standard of infrastructure for walking and cycling do not have corresponding facilities that they may walk or cycle to and vice versa.